Analisis Efektivitas Pelatihan Sequence of service dalam Mempersiapkan Mahasiswa untuk memasuki Industri Perhotelan - Natal Olotua Sipayung; Dailami .; Rezki Alhamdi; yusakh yama Langi (CV. ITTC INDONESIA, 2025)
This study aims to examine the effectiveness of sequence of service training provided to students of the Food and Beverage Management Study Program at Politeknik Pariwisata Batam in preparing them to enter the hospitality industry. Sequence of service, as a guideline for the sequence and steps that must be followed in serving guests—from their arrival until they leave the restaurant—is a crucial factor in determining guest satisfaction during their visit. Satisfied guests are more likely to return, whereas dissatisfied guests tend not to come back, which directly affects the profitability of hospitality businesses.This research is motivated by the growing demand for qualified human resources in the hospitality industry, particularly in the Food & Beverage (F&B) sector. To meet this demand, it is essential to prepare well-trained personnel who can respond effectively to guest needs.This study employs a qualitative descriptive method using techniques such as observation, interviews, and documentation. Based on the analysis of several factors influencing the effectiveness of training—namely training design, teaching methods, participant engagement, management support, evaluation and feedback, relevance to industry needs, and post-training support—it can be concluded that the training conducted at the Food and Beverage Management Study Program of Politeknik Pariwisata Batam is effective and aligned with hospitality industry standards. This is evidenced by students’ readiness to enter the hospitality industry and their successful placement in internationally standardized hotels both domestically and abroad.